Anne Conway: imagination and reason in the natural philosophy - Benítez, Viridiana Platas (Anales del Seminario de Historia de la Filosofía, 2025)
The main topic of this paper is the poetical use of the imagination in science in the context of Early Modern Philosophy. Recently studies such as Toledo (2022) and Chico (2018) have pointed out the role of the imagination in the formulation of scientific hypotheses, as well as the forerunners in the history of philosophy. Therefore, to endorse this posture, it is important to stand that in The Principles of the Most Ancient and Modern Philosophy (1690) of Anne Conway converges natural philosophy and theology in the poetic use of imagination, that is the potency to create images through rational thought that enlarge, favor, or state the thesis about the natural world. In order to establish our analysis, the paper is divided into two parts: the first explains the methodological sense of the poetical use of imagination for Conway and its relationship with the metaphysical principles of natural philosophy. Afterward, two theological-cosmological problems that are illustrated by two images are analyzed: the wheel with a statical center and the infinite stair.
Keywords: images; natural philosophy; poetical use of the imagination; reason; vitalism